Implementing Inflation Targeting Institutional Arrangements, Target Design, and Communications - Peter, Marcel (International Monetary Fund, 2006)
Transparency is a central element in most aspects of the design and operation of inflation targeting regimes. This paper focuses on three elements of inflation targeting most closely associated with transparency: (i) the institutional arrangements supporting inflation targeting; (ii) the specification of the inflation target; and (iii) the central bank''s policy communications. The paper is primarily aimed at providing practical advice to countries planning to develop an inflation targeting framework, but many of the issues are relevant for any credible, independent monetary policy